Fundamentalisme Dan Gerakan Radikal Islam Kontemporer(Kasus Jama'ah lslamiyah di Indonesia) - Huda, Miftahul (ULUL ALBAB Jurnal Studi Islam, 2004)
The phenomenon of fundamentalism and radicalism at least can be seen in the case of Jemaah Jslamiyah in Indonesia. Whether or not Jemaah Islamiyah has a link with Al-Qaeda headed by Osama Bin Laden, obviously its movement has affiliations not only in Indonesia, but also in Malaysia, Singapore, and South Philippine, and even in Thailand, Burma, and Brunei. Jemaah lslamiyah is believed to be established by Abdullah Sungkar in Malaysia in /994/1995 for the aim of establishing an Islamic State. Jemaah lslamiyah is the realization of Hybrid ideology inspired by some other movements, such as Egypt Radical Moslem, Darul Islam Movement, Dewan Dakwah Islamiyah Indonesia (DDI). This movements view the effort of Christian missionary as a threat to Islam.